The Relationship Between Waiting Time, Anxiety Levels, and Hemodynamic Status in Preoperative Patients at Purwokerto Islamic Hospital - Widya Pangastuti; Susana Widyaningsih (Proceedings Series on Health & Medical Sciences, 2026)
Background: Anxiety is an emotional response from individuals that describes a state of worry, anxiety, fear and unease accompanied by various life situations from any aspect as part of a pain disorder. Method: This research uses a correlational analytical research design, using a cross-sectional approach. The population and sample used were 56 respondents using the consecutive sampling method. The statistical test used is Spearman's rank. Results: This study shows that the majority of respondents were aged 18 – 28 years (32.1%), male (50%), completed high school/vocational school (46.4%), type of general anesthesia (50%), and type of minor surgery (100%). The results of the Spearman's rank test showed a significance value with a p value <0.05, which means that there was a significant relationship between waiting time and anxiety levels and hemodynamic status of preoperative patients during the waiting time period. Conclusion: There is a relationship between the waiting time period and the level of anxiety and hemodynamic status of preoperative patients at Purwokerto Islamic Hospital.